Lexinlexikonen och översättaren - Dahl, Adolf (LexicoNordica, 1999)
One of the new features of Lexin is the concept of a common data-base used to serve several dictionaries. Admittedly, this has been done before, but never without a cer-tain amount of adaptation to each language. The use of a common data-base saves time and money. It stands to reason that this procedure inevitably has drawbacks as well. The author argues that the translators should have a more active role in sug-gesting improvements. Another problem in Lexin is the presentation of compound words. The last ele-ments in words are listed in places where they are hard to find, which means that they are effectively "lost" for the user. Cross classification is suggested as an improvement. A third problem concerns the inclusion of new information in new editions of the Lexin dictionaries. The author points out the need for an editor who is responsible for the adaption of new data (from different sources) to the original framework of the basic Swedish dictionary and who is also responsible for the proofreading.